Some remarks on the social and economic backsliding and the foreign sector stability - Carvalho, Miguel; Carneiro, Vinícius (Brazilian Keynesian Review, 2022)
The purpose of this note is briefly indicate the most general sense of the main internal and external trends observed for the Brazilian economy after the economic crisis that started in 2015 until 2021. It is argued that this economic crisis is the deepest and longest in history of Brazil, which resulted in the generalized regression of the country’s socioeconomic indicators during the period. On the other hand, externally, we point out that between 2015 and 2021 there was no corresponding reduction in import capacity or deterioration in Brazil’s external solvency indicators, factors that could justify the extension of the crisis experienced by the country in these years.